All that Glisters Is Not Gold .... - Freny Karjodkar (Wolters Kluwer Medknow Publications, 2004)
Hot gold, antique gold a prized possession was suddenly found 'hot' enough to make the Geiger Counter Needle jump off the scale..... Redness on the ring finger may turn out to be more serious than a simple sensitivity to jewellery.